Integrated Analysis of circRNA-miRNA-mRNA-Mediated Network and Its Potential Function in Atrial Fibrillation - Wei, Feiyu; Zhang, Xi; Kuang, Xiaohui; Gao, Xiaolong; Wang, Jing; Fan, Jie (Frontiers in Cardiovascular Medicine, 2022)
Background: Atrial fibrillation (AF) is one of the most prevalent arrhythmias characterised by a high risk of heart failure and embolic stroke. Competing endogenous RNA network has been reported to play an important role in cardiovascular diseases. The main objective of the present study was to construct a circRNA–miRNA–mRNA-mediated network and explore the potential function in AF. Method: The microarray data of circRNA, miRNA and mRNA in AF were downloaded from the Gene Expression Omnibus database. The RobustRankAggreg method was used to screen the different expression circRNAs(DECs). Then the circRNA–miRNA–mRNA-mediated network was constructed by using CircInteractome database and miRWalk online tool. Quantitative real-time polymerase chain reaction was used to detect the circRNA expression level in plasma. The left atrial fibrosis was evaluated with the left atrial low voltage area by using left atrial voltage matrix mapping. Results: Three DECs (hsa_circRNA_102461, hsa_circRNA_103693 and hsa_circRNA_059880) and 4 miRNAs were screened. Then a circRNA–miRNA–mRNA-Mediated Network was constructed which included two circRNAs, 4 miRNAs and 83 genes. Furthermore, the plasma’s hsa_circ_0070391 expression level was confirmed to be upregulated and positively correlated with left atrial fibrosis in AF (r=0.88, P<0.001), whereas hsa_circ_0003935 was downregulated. Moreover, the ROC curve analysis revealed hsa_circ_0070391 and hsa_circ_0003935 could differentiate AF from the healthy controls with an AUC of 0.95 (95% sensitivity and 90% specificity) and 0.86 (70% sensitivity and 75% specificity), respectively. Finally, the free of atrial tachyarrhythmia rate was dramatically lower in the hsa_circ_0070391 high expression group than in the low expression group post catheter ablation (70.0% vs. 90.0%, p=0.04). Conclusion:This study provides a novel insight to further understand the AF pathogenesis from the perspective of the circRNA–miRNA–mRNA network, suggesting that plasma circRNAs could serve as a novel atrial fibrosis and prognosis biomarker for AF.